ANALISIS KESALAHAN SISWA KELAS XI MIA 1 SMA NEGERI 1 SOJOL DALAM MENYELESAIKAN SOAL FUNGSI KUADRAT - Hasriadi, Hasriadi; Hasbi, Muh.; Hadjar, Ibnu (Universitas Tadulako, 2023)
This study aims to obtain a description of the errors made by students of class XI MIA 1 SMA Negeri 1 Sojol in solving Quadratic Function questions. This type of research is a descriptive research with a qualitative approach that describes the mistakes of class XI MIA 1 students of SMA Negeri 1 Sojol in solving quadratic function questions. The subjects in this study were students of class XI MIA 1 SMA Negeri 1 Sojol consisting of two students. Data collection was carried out by assignments and interviews. The results showed that the mistakes made by students according to the Castolean Stages analysis method contained three types of errors, namely (1) Conceptual errors made by students in the form of students not being able to use the rules correctly in determining or writing the intersection point of the graph with the y axis where to write the answer y = (0,-12) which should be written is the intersection point with the y axis is (0,-12), (2) the procedural error made by the student in the form of the student being wrong in writing the coordinates of the intersection point with the x axes where to write the final result (-6,6) and (2,0) who should write answers (-6,0) and (2,0) and write answers (-6,2) who should write answers (-6,0) and (2 , 0) and the student could not solve the problem, (3) a technical error was made in the form of an error in performing arithmetic operations in determining the peak point.